Correlate of Savings Attitude and Generational Poverty as Mediated by Financial Literacy: Evidence from Ghana - Adu, Bismark Owusu-Sekyere; Peprah, Williams Kwasi (International Journal of Economics and Financial Issues, 2025)
This study examines the mediating role of financial literacy between savings attitudes and generational poverty in Ghana. Generational poverty is a significant issue in Ghana, with a multidimensional poverty rate of 45.6% and a consumer expenditure poverty rate of 23.4%. The problem persists due to low financial literacy and poor savings attitudes, which hinder economic growth and development. The research employed a quantitative methodology, utilizing a series of regression analyses to test the mediation effects of financial literacy. A correlational design was adopted to assess the relationships between the variables. The study’s population included 400 individuals from the five regions in the northern part of Ghana, particularly focusing on rural areas with high poverty rates. A stratified random sampling technique was used to select participants, ensuring diverse representation. Results indicated that a positive savings attitude significantly reduces generational poverty, with financial literacy playing a substantial mediating role. The findings revealed that financial literacy accounted for 21.1% of the total effect, highlighting its importance in fostering effective saving behaviors. The study concludes that enhancing financial literacy is crucial for improving savings attitudes and reducing generational poverty. Practice recommendations include implementing comprehensive financial education programs, conducting community-based financial literacy workshops, and integrating financial literacy into school curricula. Policy recommendations advocate for a national financial literacy strategy, creating incentives for saving and supporting financial education initiatives. Theoretically, future research should incorporate financial literacy into economic models, conduct longitudinal studies to assess long-term impacts and explore cultural influences on saving behaviors.